Arish: Palm-Leaf Architecture - Piesik; Sandra (Thames & Hudson, 2012)
An in-depth survey of palm-leaf architecture in the UAE; its history and traditions, its present and its future. Traditional buildings made from the leaves of date palms have provided shelter from the extreme climate of the Arabian peninsula for generations. One of the few forms of vegetation in these hot and sandy conditions, palm leaves have been used in ingenious ways to create habitable structures that have endured for generations. In many regions this is referred to as Arish. Arish: Palm-Leaf Architecture celebrates this unique indigenous building and craft tradition and provides the foundation for a genuine understanding of the region, critical in the context of the fast-developing global economies they have become today. Dr Sandra Piesik is an architect and a researcher specializing in technology development and transfer. She has worked extensively in the Middle East on projects that reconnect traditional knowledge systems with modern applications, and has led successful research, development and deployment studies on the adaptation of date palm leaf architecture for modern use, which resulted in an award-winning project endorsed by the UNCCD and this book.
English
Keywords: NA4100-4145 Special classes of Buildings- Classed by Material